Performance comparison of automotive air conditioner using various refrigerants - Serevina, Vina (2015)
Working fluid of R134a is widely used as a refrigerant in automotive air conditioner. This refrigerant has a good performance on the automotive air conditioner. However, because R134a still has a high global warming potential, this refrigerant must be reduced and replaced by environmentally friendly refrigerants. Hydrocarbons of R600a, R290 and their mixtures are widely used as substitute refrigerant. These refrigerants are natural fluids, no effect on the climate, inexpensive and readily available. There are three performances will be discussed in the present study, namely COP, mass flow rate and compression ratio. The present study investigates the effect of three refrigerants, i.e. R134a, R600a and R290 on the performance of automotive air conditioner. The results show that the COP of R600a is higher than those R134a and R290. For the same cooling capacity, the mass flow rate of R600a is approximately 50% of R134a for all ambient temperatures. In addition, the compression ratio of R600a is lower than that of R134a.